Use of biosimilars in inflammatory bowel disease: a position update of the Italian Group for the Study of Inflammatory Bowel Disease (IG-IBD). Issue 5 (May 2019) - Fiorino, Gionata; Caprioli, Flavio; Daperno, Marco; Mocciaro, Filippo; Principi, Mariabeatrice; Viscido, Angelo; Fantini, Massimo Claudio; Orlando, Ambrogio; Papi, Claudio; Annese, Vito; Danese, Silvio; Vecchi, Maurizio; et al.
Abstract: The first infliximab biosimilar for the treatment of inflammatory bowel disease (IBD) was introduced in 2013, and today eight anti-TNF alpha biosimilars (three for infliximab and five for adalimumab) have been approved and licensed by the European Medicines Agency. Biosimilars present great potential in terms of cost saving and possible consequential reinvestment in the health care system. The increasing knowledge about the process of biosimilar development and use in IBD and the publication of many prospective clinical studies and real-life clinical experiences have progressively changed the point of view of IBD physicians. In the present position paper, the Italian Group for the Study of Inflammatory Bowel Disease present and discuss their updated statements and positions on this topic, with emphasis on the concepts of biosimilarity and extrapolation across indications, safety and immunogenicity, interchangeability and switching, automatic substitution, and, finally, patient education about biosimilars.